Performance of Ti/TiO2-ZIF-67 photoanode under LED irradiation applied to the photoelectrodegradation of the antidepressant venlafaxine (VEN) in municipal wastewater effluent - Irikura, Kallyni [UNESP]; Rojas-Mantilla, Hernán Dário [UNESP]; Ayala-Durán, Saidy Cristina [UNESP]; Souza, João Carlos de [UNESP]; Rossini, Eduardo Luiz [UNESP]; Salazar-González, Ricardo; Zanoni, Maria Valnice Boldrin [UNESP] (Elsevier, 2025)
This work describes the direct deposition of ZIF-67 metal-organic framework (MOF) onto Ti/TiO2 nanotubes forming a photoanode for the degradation of the antidepressant Venlafaxine (VEN). This material combines the excellent characteristics of ZIF-67 MOF in enhancing photocatalytic reduction and oxidation reactions induced by UV LED irradiation, as well as the storage of VEN molecules in its pores. Ti/TiO2-ZIF-67 features an eco-friendly technology for degradation of pharmaceutical micropollutants such as antidepressants. The photoanode was prepared, characterized and applied in the degradation of VEN by photocatalysis (PC), electrocatalysis (EC), photolysis (PL) and PEC processes. PEC process presented the best performance when compared to the others processes in both simulated solutions and real wastewater, achieving 100% and 89% degradation of VEN after 60 and 90 min, with TOC removal rates of 50% and 4%, respectively. The lower mineralization rate suggests that the degradation of VEN in complex matrices such as that of real wastewater produced recalcitrant by-products that are difficult to convert into CO2 and H2O. Zeta potential measurement showed that at pH 6 and 8 there is an effect of attraction of opposite electrostatic charges between the surface of ZIF-67 (positive) and VEN (negative), favoring the degradation of VEN in this pH range. The good performance of the Ti/TiO2-ZIF-67 can be attributed to the formation of the Z-scheme heterojunction between the TiO2 nanotubes and the ZIF-67 MOF which contributed to a lower rate of electron-hole (e−/h+) pairs recombination, favoring VEN degradation mainly to higher generation of •OH radical and less contribution of O2•- superoxide produced by UV irradiation forming some degradation by-products through demethylation and oxidation reactions.
Keywords: Antidepressant; Eco-friendly technology; Metal-organic framework; Photoelectrocatalytic; Titanium dioxide nanotubes